Precise positioning of cancerous cells on PDMS substrates with gradients of elasticity - Raczkowska, J. (Biomed Microdevices, 2016)
In this work the novel method to create PDMS substrates with continuous and discrete elasticity gradients of different shapes and dimensions over the large areas was introduced. Elastic properties of the sample were traced using force spectroscopy (FS) and quantitative imaging (QI) mode of atomic force microscopy (AFM). Then, fluorescence microscopy was applied to investigate the effect of elastic properties on proliferation of bladder cancer cells (HCV29). Obtained results show that cancerous cells proliferate significantly more effective on soft PDMS, whereas the stiff one is almost cell-repellant. This strong impact of substrate elasticity on cellular behavior is driving force enabling precise positioning of cells.